PENGGUNAAN JENIS-JENIS HIJAUAN PAKAN TERNAK RUMINANSIA DI KABUPATEN TIMOR TENGAH SELATAN - Vivin Elmiyati Se'u; Yelly Magdalena Mulik (Politeknik Pertanian Negeri Kupang, 2022)
The potential of land and pastures is very abundant, especially in South Central Timor Regency. However, the maintenance system is still conducted using extensive-traditional (semi-intensive) methods, that is, grazing is carried out in natural pasture where the cattle are left free to graze and after that the cattle are put back in cages. Therefore, farmers must provide forage for their livestock. The purpose of this study was to analyze the potential use of forage for ruminants in South Central Timor Regency. Primary data had been obtained through interviews using questionnaires and direct observations. Respondents in this study were 94 breeders located in the districts of North Mollo, Noebeba and South Amanuban. Results of the study showed that the types of forage fodder in South Central Timor Regency consisted of natural grass, superior grass, tree legumes and rumbah. In addition, farmers also used agricultural crop wastes as animal feed. Key Words: Forages, Pasture, South Central Timor Regency.